Sleep‐disordered breathing in pediatric heart transplant recipients. (26th October 2020) - Powell, Weston T.; Chen, Maida; Kraft, Danielle; Albers, Erin
Abstract: Background: Sleep‐disordered breathing is commonly found in adults with heart failure both before and after HTx. Untreated sleep‐disordered breathing post‐transplant has been linked to late graft dysfunction, reduced quality of life, and increased morbidity. Sleep‐disordered breathing has not been investigated in pediatric HTx recipients. Methods: We conducted retrospective review of patients <21yo who underwent primary HTx at our center from 2009 to 2019 to describe clinical characteristics, cardiac history, and PSG results. Results: One hundred and fifty patients were included; 60% had congenital heart disease, and 40% had cardiomyopathy. Fifty patients had PSG performed at median age of 6.1 years. Forty‐one were referred for symptoms of sleep‐disordered breathing. Obstructive sleep apnea was diagnosed in 45 patients and central sleep apnea in 3 patients. Of those with first PSG post‐transplant (n = 36), median AHI was 9.1/h, and 19 (53%) were diagnosed with moderate or severe sleep apnea. Patients diagnosed with obstructive sleep apnea on PSG had more post‐transplant ventilator days (median 3 vs 2 days, P  < .05) and longer post‐transplant lengths of stay (median 28 vs 22 days, P  < .05). Conclusions: In this single‐center cohort of pediatric HTx recipients, sleep‐disordered breathing was common and associated with longer peri‐transplant respiratory support and length of stay. Given the high incidence of moderate and severe OSA detected in this population, clinicians should regularly screen for SDB and consider PSG testing more frequently in children who have undergone HTx. Further study into the long‐term impact of sleep‐disordered breathing in pediatric HTx recipients is needed.